2022
DOI: 10.1111/aec.13249
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific density plays a pivotal role in shaping sapling community in highly fragmented subtropical forests

Abstract: Tropical and subtropical regions shelter high levels of biodiversity. A combination of biological, environmental and anthropogenic factors influences tree community diversity and composition. Here, we use data from the IFFSC project to test the effect of conspecific and heterospecific density dependence, canopy cover and distance to edge on saplings populations of 229 woody species in 159 plots distributed across three forest types in Southern Brazil. All plots were measured twice with a standardized time inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Vegetation research covering South America, Africa and Australia is also included in this issue. In Brazil, data from the Brazilian national forest inventory, Forest and Floristic Inventory of Santa Catarina (IFFSC) was used to assess sapling community dynamics over three forest types covering 95 000 km 2 (da Silva et al, 2022). They found that there is a strong relationship between conspecific density in sapling survival and growth, which is particularly important when the forests are highly fragmented.…”
mentioning
confidence: 99%
“…Vegetation research covering South America, Africa and Australia is also included in this issue. In Brazil, data from the Brazilian national forest inventory, Forest and Floristic Inventory of Santa Catarina (IFFSC) was used to assess sapling community dynamics over three forest types covering 95 000 km 2 (da Silva et al, 2022). They found that there is a strong relationship between conspecific density in sapling survival and growth, which is particularly important when the forests are highly fragmented.…”
mentioning
confidence: 99%